The Village Financial Management Policy To Achieve Good Governance - Sulistyaningsih, Endang; Adi, Pudja Pramana Kusuma; Sayekti, Lady Laduni (Jurnal Ilmiah Dunia Hukum, 2024)
This study aims to analyze and investigate Indonesia's response to the Rohingya refugee crisis and examine its compliance with international law in addressing complex humanitarian challenges while tracing the history of Rohingya refugees in Indonesia since 2017. The research focuses on recent developments, including the surge in refugee arrivals and increasing tensions between newcomers and local residents. This study employs normative juridical research emphasizing a case study approach, utilizing secondary data analyzed qualitatively and presented using descriptive qualitative analysis techniques. The results indicate that Indonesia has principally committed to international law concerning refugees through concrete actions, diplomacy, and dialogue. However, the handling of Rohingya refugees in Indonesia, as regulated by PERPRES 125/2016, does not fully align with international legal principles, particularly the non-refoulement principle of the 1951 Convention. Refugees are considered illegal immigrants with temporary accommodation ending in relocation or repatriation. Further efforts are needed to ensure treatment aligns with human rights norms and provides adequate protection, including the right to employment, which is challenging due to the scarcity of job opportunities for Indonesian citizens themselves.